Mortality of Mucormycosis during Coronavirus Disease Pandemic - Samah Abbas; Usama Salim Hassan; Mustafa Shamkhi Aood (Medical Journal of Babylon)
Background:Acute invasive fungal rhinosinusitis is an aggressive, mutilating, and in many cases life-threatening infection that results in rapid devitalization of tissues in the area of the nasal cavity and paranasal sinuses. Diabetic ketoacidosis, renal impairment, and hematological malignancies used to be the main predisposing factors for this serious infection. During the second wave of the pandemic of coronavirus disease (COVID-19), there has been an increment in these cases, in a manner that has not been witnessed before, and hence the interest in studying this topic. Objectives:Review of management outcomes and mortality in patients diagnosed with “possible invasive fungal rhinosinusitis” during the 2nd wave of COVID-19 pandemic and compare these with the outcomes observed before the pandemic in Iraq and other countries. Materials and Methods:A cross-sectional study of all patients with clinically possible invasive fungal rhinosinusitis (30 patients) presenting or referred to the ear nose and throat outpatient unit during the period from June 1st 2021 to December 31st 2021. Results:30 patients were included, 53.3% male, 73.33% had mucormycosis following COVID-19 infection. Diabetes was the underlying condition in 57.67% of the cases. Fever, facial pain, nasal obstruction and headache were the most prevalent symptoms at presentation. The mortality rate was 16.7%. Conclusion:A reduced mortality rate was observed despite the increased number of cases, and this is mostly related to the early initiation of antifungal therapy.